Kisah Nabi Nuh dalam Al-Qur'an - Nabila SR; Anisa Muhammad; Aditya Saputra Ahmad; Mustaqimah Hikam (JURNAL ILMU AL-QUR'AN DAN TAFSIR NURUL ISLAM SUMENEP, 2024)
This article examines the story of the Prophet Noah based on the perspective of the Qur'an from several verses implied in the chapters contained in the Qur'an. This research was conducted to re-interpret the story of the Prophet Noah and be able to be implemented into everyday life. This research was conducted using a literature review and collecting various literature related to the story of the Prophet Noah. From the literature research, various kinds of wisdom and interpretations of the story of the Prophet Noah were also presented. Keywords: Story, Prophet Noah, Al-Qur'an